Studi Eksperimental Turbin Darrieus Dengan Sudu Overlap - Kaprawi Sahin; Fajri Prawira (Jurnal Rekayasa Mesin, 2020)
The need for energy is needed at this time. Energy is useful for daily life that can be utilized in human survival. For that we need energy that can be utilized by humans, one of them is wind energy. The Darrieus turbine is a vertical axis wind turbine (VAWT) wind turbine that has high efficiency and is capable of producing large enough torque at high wind speeds and rotations. The working principle of the darrieus turbine utilizes wind that blows the blades where the turbine can rotate with high wind speeds, and does not have good self starting so that assistance is needed at low wind speeds. the purpose of this study is the utilization of overlap on the darrieus blade can rotate low wind speeds and have a good self starting. The darrieus blade study was used only in wind tunnels with a blade thickness of 20 mm, width of 50 mm and blade length of 200 mm. The range of wind speeds used in the wind tunnel ranges from 7 m / s, 9 m / s, 11 m / s. Overlap research conducted with a distance of 4 mm blade.